MODELING TIDAL CURRENT OF BANTEN BAY DURING TRANSITIONAL MONSOONS 2015-2016 - Ahmad Bayhaqi; Ulung Jantama Wisha; Dewi Surinati (Jurnal Segara, 2018)
Hydrodynamic condition of Java sea as a part of Indian-Pacific throughflow system influenced by monsoon will affect the condition of Banten Bay such as tidal current. Bordered by Java Sea makes Banten Bay preoccupied with fisheries and shipping activities, so the information regarding current pattern that is tidal current is very necessary. This study aims to simulate the tidal current pattern using flow model fm as a numerical approach. Two-dimensional hydrodynamic model was employed to perform the simulation of tidal current. Model was validated by using current and tidal observation data which was taken on September 2015 and April 2016. The result shows that the current moves southwestern toward the land during high neap and high spring tidal conditions ranged 0 - 0.142 m/s at the first transitional monsoon and 0 - 0.153 m/s at the second transitional monsoon respectively. During low spring tidal condition for both transitional monsoons, the current flowed northwestward on west side and northeastward on east side within the bay ranged 0 - 0.137 m/s and 0 - 0.127 m/s respectively. The hydrodynamic conditions of Banten Bay are slightly different between 2 transitional seasons, especially for the current speed and direction. Those conditions induce a different transport mechanism, resulting in unstable accretion and abrasion along Banten Bay coast.